EVALUATING AN INDIVIDUALIZED SCIENCE PROGRAM FOR COMMUNITY COLLEGE STUDENTS. - Tuckman, Bruce W.; Waheed, Mohammed A. (Journal of Research in Science Teaching, 1981)
The article describes a study which compares the efficacy of individualized instruction to traditional instruction of science among community college students. The study indicates the effectiveness of individualized instruction in teaching Basic Science to these students. It improves their accomplishments and attitudes towards science. A study was cited which concluded that students in the individualized class had a lower course withdrawal rate. Due to the individualized approach, unprepared students found it easier to master a small section of learning at a given time.